Ecotheology in the Holy Scriptures: A Study of the Intertextuality of the Qur’an and the Bible - Fadhilah Siti Ramdina Bowode (Jurnal Studi Agama, 2025)
This study offers ecotheology as an approach that considers the reciprocal relationship between religion and nature. This study attempts to build a dialogue between holy books by examining ecotheological narratives regarding the concept of the environment. This research was conducted to answer several academic questions, namely regarding the concept of ecotheology contained in the Qur'an and the Bible, as well as to examine the comparative patterns of ecotheological narratives in each holy book. The results of this study show that the Qur'an and the Bible both teach compassion for nature through spiritual dimensions and the basis of faith.